Body Building Music: The Kinase Instalation - Monnazzi, João; Faria, Regis (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação Musical, 2019)
Thinking on the congruencies between music and sports, we propose with this art installation some novel paths and connections for music production in a little explored field, in the interdisciplinarity with sports. Some similarities in the acting of musicians and athletes, such as the need of technical domain through discipline and practice. A musician who wants to develop her/his technical skills needs to follow a hard routine of practical studies, focusing in improving motor abilities with the proposing to play the piece in the better way possible. This process has a close proximity with the athlete’s during their preparation. Hours of intense practice to improve some motor skills that can enable them to improve their performance. The disciplines can be interpolated in a way that we can argue: there is always something physical on a music interpretation, as well as there is always something artistic in a sport competition. In the inner area between art/music and sports some modalities are easier to verify this symbiosis, as in the choreographic sports. These modalities are evaluated by both physical and artistic parameters. Our work focus in a particular sport modality that has a part of scoring which is evaluated through a choreographic routine: The Bodybuilding.